Pengaruh Besar Pemberdayaan Lembaga Adat Oleh Badan Narkotika Provinsi Sumatera Barat Sebagai Pencegahan Penggunaan Narkotika Terhadap Pengulangan (Residivis) - Utama, Rahmides; Khairani, Khairani (Nagari Law Review, 2025)
This research aims to determine the big influence of empowering traditional institutions by the Narcotics Agency of West Sumatra Province as an effort to prevent narcotics use against recidivism. The Narcotics Law mandates that the eradication of narcotics crimes be carried out through the involvement and participation of the community in various activities to prevent or control narcotics crimes, especially in cases of repetition of criminal acts or recidivism. This research is normative juridical supported by empirical juridical and descriptive analysis. The data used is primary, secondary and tertiary legal materials. The results of the study show that the empowerment of traditional institutions by the West Sumatra Province Narcotics Agency has a major influence in preventing repetition of narcotics crimes or recidivism. Through an approach based on local wisdom, social rehabilitation, character development and community support, traditional institutions can play an effective role in helping criminals not fall back into criminal behavior. The involvement of traditional institutions in the rehabilitation process strengthens social ties and ensures that offenders receive the support they need to live a better life and stay away from narcotics. Although empowering traditional institutions has great potential in preventing narcotics and the repetition of criminal acts, there are several obstacles that must be overcome to achieve success. Obstacles such as lack of understanding, limited resources, social stigma, and resistance to change need to be overcome with a careful approach and involving all relevant parties. Empowerment programs for traditional institutions must be adapted to the local cultural context and supported by good coordination between the government, traditional institutions and the community to create an environment free from drug abuse.